Pengaruh Inovasi Teknologi pada Dinamika Kehidupan Sosial: Literature Review - Ajeng Fitriyadi Ningsih; Bambang Sulistiono; Nely Anawati; Didik Tri Setiyoko (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
This research aims to examine the influence of technology on the dynamics of social life. Through a literature review research method, this research found that technology has brought significant changes in the way humans interact, communicate and socialize. On the one hand, technology makes it easier to access information, expands social networks, and encourages innovation. However, on the other hand, technology can also trigger social isolation, raise privacy issues, and change existing social norms. This research concludes that the influence of technology on social life is complex and multidimensional, so further studies need to be carried out to understand its long-term impact.